Development of idraparinux and idrabiotaparinux for anticoagulant therapy - Harenberg, Job (Thrombosis and Haemostasis, 2009)
Idraparinux is an analogue of fondaparinux binding with high affinity to antithrombin. It was designed for weekly, rather than daily, administration, with an exceptionally long half-life. One potential problem with small heparin-like fragments of this type is the difficulty of neutralising excessive activity in the case of sideeffects or overdose. The efficacy of idraparinux was was proven in clincial studies with patients suffering from venous thromboembolism (VTE) or atrial fibrillation. Due to major bleeding events during treatment for more than six months the development of idraparinux was stopped. Idrabiotaparinux has an attached biotin moiety at the non-reducing end unit, which allows its neutralisation with avidin, an egg-derived protein with low antigenicity. This compound is currently investigated in clinical trials for prevention of recurrent VTE in patients with acute pulmonary embolism. The future of idrabiotaparinux depends also on the safety and efficacy of avidin.
Keywords: Idraparinux; idrabiotaparinux; thrombosis; atrial fibrillation